Geomorphology in the Anthropocene - Goudie, Andrew; Viles, Heather A. (Cambridge : Cambridge University Press, 2016)
The Anthropocene is a major new concept in the Earth sciences and this book examines the effects on geomorphology within this period. Drawing examples from many different global environments, this comprehensive volume demonstrates that human impact on landforms and land-forming processes is profound, due to various driving forces, including: use of fire; extinction of fauna; development of agriculture, urbanisation, and globalisation; and new methods of harnessing energy. The book explores the ways in which future climate change due to anthropogenic causes may further magnify effects on geomorphology, with respect to future hazards such as floods and landslides, the state of the cryosphere, and sea level. The book concludes with a consideration of the ways in which landforms are now being managed and protected. Covering all major aspects of geomorphology, this book is ideal for undergraduate and graduate students studying geomorphology, environmental science and physical geography, and for all researchers of geomorphology.
Machine generated contents note: Preface; 1. Introduction to the Anthropocene and anthropogeomorphology; 2. Drivers of anthropogeomorphological change; 3. Construction and excavation; 4. Subsidence in the Anthropocene; 5. Weathering processes in the Anthropocene; 6. Hillslope processes in the Anthropocene; 7. Fluvial processes and forms in the Anthropocene; 8. Aeolian processes and forms in the Anthropocene; 9. Coastal processes and forms in the Anthropocene; 10. Cryospheric processes and forms in the Anthropocene; 11. Conclusions on the relationships between geomorphology and the Anthropocene; References; Index.
Title from publisher's bibliographic system (viewed on 27 Oct 2016).
Keywords: Geomorphology